Ten Reasons Why Prospective Randomized Studies in Surgery Are Flawed and Fundamentally Different From Drug Trials - Shin, Alexander Y; de Pinal, Francisco (The Journal of hand surgery (American ed.), 2025)
Prospective randomized controlled trials are widely regarded as the gold standard for evaluating therapeutic interventions. Although this model is appropriate for drug development, its application in surgical research has proven challenging and, in many cases, misleading. Surgery involves complex interactions between technical skill, patient variability, and intraoperative decision-making that cannot be easily standardized or controlled. This article outlines 10 reasons why prospective randomized studies in surgery are fundamentally different from drug trials, highlighting methodological, ethical, and practical concerns. Recognizing these distinctions is critical to developing more appropriate and context-sensitive research frameworks for surgical evaluation.